ANALYZED PASAK BUMI AND DORSIH AS MEDICINE PLANTS BASED ON LOCAL KNOWLEDGE IN DOLOK MARAWA VILLAGE, SILOU KAHEAN DISTRICT, SIMALUNGUN DISTRICT - Farid Aulia; Prinsi Rigitta (Jurnal Scientia, 2023)
As part of traditional medicine, the Dolok Marawa community has a type of treatment that is proven to be able to treat various diseases. The treatment is called Pasak Bumi and Dorsih. Pasak Bumi is an important part of the community's traditional medicine which has high efficacy in treating antimalarial diseases, preventing breast cancer, insecticidal ingredients increasing the hormone testosterone, and preventing osteoporosis. The use of pegs has also been carried out by local communities in Riau, Lampung and Belitung. While dorsih is known as traditional medicine in treating stomach ulcers, the treatment method can be in two ways, namely first directly taking the heat from the stem by slashing the stem and then removing the sap and get the juice directly to drink and the second way is to take a few leaves of dorsih and then puree it and boiled after that the water is taken twice a day on a regular basis. The research used through in-depth interviews, participatory observation. This activity will later become a reference for the surrounding community in finding a variety of traditional medicines derived from medicinal plants that live around the community.